Biomimetics nature-inspired design and innovation - Primrose, S. B. (Wiley Blackwell, 2020)
"At its simplest, biomimetics is the design and production of materials, structures, and systems that are modelled on biological entities and processes. The concept of biomimetics stems from the realisation that microbes, plants and animals have been continuously evolving to cope with environmental and other challenges. They already have solved design challenges associated with vision, movement in diverse environments, temperature control, and detection of predators and/or prey in myriad ways over millions of years of evolution, providing rich opportunities for development of biomimetic and bioinspired materials. The diversity in form and function of living things is such that they have evolved solutions to most of the challenges that face humans today"--